Factors That Influence the Income of Shallot Farmers in Tampo Village, Anggeraja District, Enrekang Regency - Jam'an, Andi; Asdar, Asdar; Idrus, Muhammad Ikram; Kismawati, Kismawati (Jurnal Ekonomi Balance, 2023)
This study aims to determine the effect of land area, production, price on the income of shallot farmers in Tampo Village, Anggeraja District, Enrekang Regency. This study uses a type of quantitative research. The research data were obtained from distributing questionnaires (primary) and several observations and direct interviews with related parties, namely farmers in Tampo Village, Anggeraja District, Enrekang Regency. The data analysis technique used is multiple linear regression analysis. The results showed that production and prices simultaneously had a significant effect on the income of farmers in Batu Noni Village, Anggeraja District, Enrekang Regency. Partially, it shows that land area has a positive and significant effect on shallot farmer income, production has a positive and significant effect on shallot farmer income and price has a positive and significant effect on shallot farmer income in Tampo Village, Anggeraja District, Enrekang Regency